Laws, leaders, and legends of the modern National Library of Medicine. - Smith KA (Journal of the Medical Library Association, 2008)
PURPOSE: The paper is an expanded version of the 2007 Joseph Leiter National Library of Medicine (NLM)/Medical Library Association Lecture presented at MLA '07, the Medical Library Association annual meeting in Philadelphia in May 2007. It presents an historical accounting of four major pieces of legislation, beginning with the NLM Act of 1956 up through the creation of the National Center for Biotechnology Information. BRIEF DESCRIPTION: The transition from the United States Armed Forces Medical Library to the United States National Library of Medicine in 1956 was a major turning point in NLM's history, scope, and direction. The succeeding landmark legislative achievements--namely, the 1965 Medical Library Assistance Act, the 1968 Joint Resolution forming the Lister Hill National Center for Biomedical Communications, and the 1988 authorization for the National Center for Biotechnology Information--transformed the library into a major biomedical communications institution and a leader and supporter of an effective national network of libraries of medicine. The leaders of the library and its major advocates--including Dr. Michael DeBakey, Senator Lister Hill, and Senator Claude Pepper-together contributed to the creation of the modern NLM.